Phenomenology and experience : new perspectives - Cimino, Antonio, 1979- (Studies in Contemporary Phenomenology, 2019)
Experience has been a pivotal philosophical topic since Greek antiquity. The phenomenological movement has also played a crucial role in the history of philosophical theories or ideas of experience. The major contributions of Husserlian and post-Husserlian phenomenology to the philosophical understanding of experience can hardly be overestimated. The ambition of this volume is to illustrate how phenomenology still remains a very fruitful approach that is essential to current philosophical and interdisciplinary debates on experience.